Theoretical Dimensions of the GDP Expenditure Structure Convergence in the Eurozone - Velichkov, Nikolay (Research Papers, 2020)
The aim of this paper is to reveal the numerous macroeconomic dimensions of the GDP expenditure structure, and based on that to demonstrate the economic importance of the convergence with respect to this structure for the Eurozone countries. In this context, it can be concluded that achieving convergence in the expenditure components of GDP for the Eurozone countries is a prerequisite for convergence of the fundamental features of their economies. This convergence concerns first and foremost the factors determining the economic growth and flow of the business cycle which is an important condition for the effective functioning of the EU's Economic and Monetary Union.
Keywords: GDP expenditure structure; Convergence; Eurozone